Synthetic molecules as DprE1 inhibitors: A patent review. (3rd August 2021) - Imran, Mohd.; A.S., Alshrari; Thabet, Hamdy Kh.; Abida,; Afroz Bakht, Md.
ABSTRACT: Introduction: In recent years, the advent of multidrug-resistant tuberculosis (MDR-TB), the extensively-resistant TB (XDR-TB), and the total drug-resistant-TB (TDR-TB) have led the community to develop new antitubercular molecules. The decaprenylphosphoryl-β-D-ribose-2ʹ-epimerase-1 (DprE1) is an established target to developed new anti-TB drugs. This enzyme is required to synthesize the cell wall of Mycobacterium tuberculosis (Mtb). Area Covered: This patent review focuses on the granted patents and patent applications related to the chemical entities developed as DprE1 inhibitors for TB treatment from the publication year of the BTZ-043 compound patent application (2007) till 30 September 2020. Expert Opinion: The DprE1 has many advantages in the development of new antitubercular molecules, for example, its location in the periplasm of the Mtb cell wall and its absence in the human body. This indicates that the DprE1 inhibitors are selective for Mtb, and their toxic and side effects on the human body may be negligible or small. Accordingly, the use of DprE1 inhibitors may be benefic for patients with drug-resistant bacteria that require long-term medication. Four molecules are in clinical trials, which could become the drugs of the future for TB-therapy.